تأثير توازن بعض العناصر الغذائية الصغرى في التربة على نمو نبات الذرة - مصطفى محمد امحمد أبووذن; نجاة العربي صالح اليسير; نوري سالم النعاس (African Journal of Advanced Pure and Applied Sciences, 2023)
This study was conducted in the city of Al-Khums, located 125 km east of Tripoli, Libya, in the year 2018. The objective of the experiment was to investigate the interactions between the nutritional elements iron and zinc, in order to determine the optimal rates of adding these elements to avoid losses in fertilizers and minimize losses in added elements. The aim was to achieve abundant production with minimal cost and reduced pollution of soil, water, and air, which is the positive goal of applied scientific research. The experiment was conducted for one agricultural season on the local variety of maize plants. Four levels of iron (0, 5, 10, and 20 milligrams per kilogram of soil) were used, while three levels of zinc (0, 5, and 10 milligrams per kilogram of soil) were applied. Iron was added in the form of EDDHA-Fe 6% iron chelate, and zinc was added as zinc sulfate. The results obtained showed that the best rate of adding iron without zinc was 10 milligrams per kilogram of soil, which achieved a yield of 92.45 grams per ear corresponding to a plant-absorbed iron concentration of 25.86 grams per ear. The best rate of adding zinc without iron was 5 milligrams per kilogram of soil, and it resulted in a yield of 51.44 grams per ear corresponding to a plant-absorbed zinc concentration of 6.03 grams per ear. The results also showed that the best levels of adding both iron and zinc together were 5 milligrams per kilogram of soil for each element, resulting in a yield of 39.24 grams per ear. In contrast, the control treatment without adding iron and zinc (0-0 rates) had a yield of 20.10 grams per ear, which was the lowest productivity obtained under the experimental conditions used. The statistical analysis revealed significant and highly significant values for the effects of interactions on dry weight and the concentration of the absorbed elements in the plants.